27 Impact of Culprit Versus Non-Culprit Angiography Strategy on Primary PCI Door to Balloon Times. (3rd June 2016) - Horne, Anna; Gunn, Julian; Iqbal, Javaid; Morgan, Kenny; Hall, Ian; West, John; Grech, Ever; Barmby, David; Wheeldon, Nigel; Storey, Robert; Richardson, James
Abstract : Background: Guidelines for ST-segment elevation myocardial infarction (STEMI) recommend primary percutaneous coronary intervention (PPCI) within 90 min of arrival in a PCI-capable hospital. Some PCI operators perform diagnostic angiography of the non-culprit artery prior to intervention ('non-culprit' strategy) while others proceed directly to the presumed culprit vessel ('culprit' strategy) reserving imaging of the non-culprit vessel until after the PCI. We evaluated the 'time cost' of each approach and their impact upon door to balloon times (D2B). Methods: All consecutive patients presenting with STEMI to a regional heart attack centre between April 2014 and March 2015 (n = 630) were included. The time from the first angiogram acquisition (culprit or non-culprit vessel) to device use (thrombectomy catheter, balloon or stent) was recorded for each strategy. Overall D2B times were analysed. Results: A culprit strategy was followed in 69/630 and a non-culprit approach in 561/630. The mean time from first image to device use was 15 mins 41s for non-culprit strategy and 8 mins 9s for culprit strategy. The non-culprit strategy therefore incurred a delay of 7 mins 32s (p < 0.01). The mean D2B time was 52 mins and 66 mins for the culprit and non-culprit strategies respectively (p < 0.05). The percentage meeting D2B time <90mins was 86% for culprit and 78% for non-culprit strategies. Percentage meeting D2B time <60 mins (which may have additional mortality benefit) was 71% and 58% for the culprit and non-culprit strategies respectively. In our cohort, mortality was significantly lower in patients with D2B <90 mins at 2.0%, versus 4.6% in those whose D2B was >90mins (p = 0.02). Conclusion: A 'culprit' PPCI strategy results in significantly shorter D2B times, facilitating institutional attainment of national guideline targets, which may translate into improved patient outcomes.